Efektivitas Sistem Manajemen Keselamatan dan Kesehatan Kerja (SMK3) dalam Upaya Menekan Angka Kecelakaan Kerja di Kota Batam - Romadona, Hanifah Ghafila; Sudirman, Lu; Syarief, Elza (Wajah Hukum, 2024)
The Occupational Safety and Health Management System (SMK3) is imperative as a preventive measure to mitigate workplace accidents within a company's environment. Indonesia has enacted legal regulations regarding SMK3, specifically Government Regulation Number 50 of 2012 concerning the Implementation of the Occupational Safety and Health Management System. Nevertheless, the existence of these regulations does not consistently enhance workers' awareness of their safety while at work. This research employs an empirical research method, gathering data through literature studies as secondary data and interviews with the safety officer of PT. GPI as primary data. The research findings conclude that PT. GPI has implemented SMK3 in Indonesia. However, the implementation of SMK3 at PT. GPI in Batam cannot be deemed effective due to the presence of workers unwilling to comply with the applied regulations, ultimately leading to workplace accidents. In addressing this situation, the company needs to enhance strictness and supervision of each worker to ensure compliance with every applicable occupational safety and health regulation.